Geo-Information Tools, Governance, and Wicked Policy Problems - Reckien, D. (2020)
The emblematic intergovernmental Group of Earth Observations (GEO) sees food, water and energy security, natural hazards, pandemics of infectious diseases, sustainability of key services, poverty, and climate change as societal challenges. We regard the abovementioned societal challenges as wicked policy problems involving multiple or unknown causes, anticipated and unanticipated effects, and high levels of disagreement among governance stakeholders concerning the nature (and even the existence) of a problem and the appropriateness of solutions. In this Special Issue, we attempt to take the pulse of how we, as geo-information scientists, tackle wicked problems in the global North and South.